Analisis Kuat Tekan dan Kuat Tarik Belah Beton Ringan dengan Substitusi Limbah Bata Ringan dan Styrofoam - Muhamad Ali Ma’sum; Sumirin Sumirin; Soedarsono Soedarsono (Syntax Corporation Indonesia, 2024)
Lightweight concrete is concrete that has a lighter density than concrete in general. Lightweight concrete is made by adding air pores to the concrete mixture. Concrete has the benefits of its constituent materials which consist of fine aggregate, water, Portland cement, coarse aggregate, and other added materials. Concrete also has a weakness, namely its high specific gravity. So the dead load on the structure will become large. Therefore, innovation in concrete technology is expected to be able to answer all the challenges of needs, one of which is environmentally friendly and has a low specific gravity, or what is called lightweight concrete. The method in the thesis consists of 2 methods, namely literature study and laboratory testing method. This laboratory testing is carried out with the aim of knowing the results of testing carried out with process stages starting from literature study, material testing, making mix designs, mixing materials, slump testing, making test objects, curing, testing compressive strength and split tensile strength then drawing conclusions . The results of the compressive strength value of the test object with the addition of 40% styrofoam and light brick had an average compressive strength of 10.85 and when the composition was reduced to 30% the compressive strength increased by 51%, namely 21.1 Mpa, whereas when the composition was reduced to 20% the compressive strength increased by 53%, namely 22.7, while the splitting tensile strength value of the test object with the addition of styrofoam and lightweight bricks of 40% had an average splitting tensile strength of 0.875 and when the composition was reduced to 30% the average splitting tensile strength increased by 13.8%, namely amounted to 1.2 Mpa, while when the composition was reduced to 20% the average splitting tensile strength increased by 18.3%, namely 1.6 Mpa.